Site- and strand-specific nicking of DNA by fusion proteins derived from MutH and I-SceI or TALE repeats - Gabsalilow, Lilia; Schierling, Benno; Friedhoff, Peter; Pingoud, Alfred; Wende, Wolfgang; Justus Liebig University Giessen (My University, 2013)
Targeted genome engineering requires nucleases that introduce a highly specific double-strand break in the genome that is either processed by homology-directed repair in the presence of a homologous repair template or by non-homologous end-joining (NHEJ) that usually results in insertions or deletions. The error-prone NHEJ can be efficiently suppressed by nickases that produce a single-strand break rather than a double-strand break. Highly specific nickases have been produced by engineering of homing endonucleases and more recently by modifying zinc finger nucleases (ZFNs) composed of a zinc finger array and the catalytic domain of the restriction endonuclease FokI. These ZF-nickases work as heterodimers in which one subunit has a catalytically inactive FokI domain. We present two different approaches to engineer highly specific nickases; both rely on the sequence-specific nicking activity of the DNA mismatch repair endonuclease MutH which we fused to a DNA-binding module, either a catalytically inactive variant of the homing endonuclease I-SceI or the DNA-binding domain of the TALE protein AvrBs4. The fusion proteins nick strand specifically a bipartite recognition sequence consisting of the MutH and the I-SceI or TALE recognition sequences, respectively, with a more than 1000-fold preference over a stand-alone MutH site. TALE MutH is a programmable nickase.
Keywords: ddc:570